Identification of new functional inhibitors of acid sphingomyelinase using a structure-property-activity relation model - Kornhuber, Johannes; Tripal, Philipp; Reichel, Martin; Terfloth, Lothar; Bleich, Stefan; Wiftfang, Jens; Gulbins, Erich (Journal of Medicinal Chemistry, 2008)
Some organic weak bases induce a detachment from inner lysosomal membranes and subsequent inactivation of acid sphingomyelinase (ASM) and thus work as functional ASM inhibitors. The aim of the present investigation was to develop a structure-property-activity relation (SPAR) model in order to specify the structural and physicochemical characteristics of probes capable of functionally inhibiting ASM. High pKa and high log P values are necessary but not sufficient preconditions for functional inhibition of ASM. The experimental data supported the requirement of an additional factor, which is necessary for functional inhibition of ASM. This factor k is related to the steric hindrance of the most basic nitrogen atom and presumably modulates the free presentation of a protonated nitrogen atom at the inner lysosomal surface. During the course of the study, we characterized 26 new functional ASM inhibitors, including doxepine 63, fluoxetine 104, maprotiline 109, nortriptyline 114, paroxetine 118, sertraline 124, suloctidil 125, and terfenadine 127. © 2008 American Chemical Society.
Created from Fastlane, Scopus look-up